AN ANALYSIS OF PHRASAL VERBS IN THE NOVEL GULLIVER’S TRAVELS BY JONATHAN SWIFT - Gina Khoerun Nisa; Jauhar Helmie; Nuraeni Susilawati (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2020)
Syntax is a branch of linguistics which is studies about patterning words into phrases, clauses, and sentences. The study about syntax is very important because many people can write but they do not know the proper structure of grammar. In this research, the researcher will focus on syntax that has to do with phrasal verbs. The title of this research is an analysis of phrasal verbs in the novel Gulliver’s travel by Jonathan swift. The purpose of this research is to find out the kinds of phrasal verbs encountered in novel Gulliver’s travel and the meaning of those phrasal verbs. The object of this research is the novel Gulliver’s travel 1926. This research will use qualitative research. In addition, this research will help the reader in enriching vocabularies and could be example or additional reference for researcher who wants to analyze phrasal verbs of the novel in their research and also could be useful for students who learn about phrasal verbs in the novel. Why the researcher uses these data since those make it easier to organize the data and it is suitable for this research. There are 30 words of phrasal verbs found in the novel as the data source. Those particles that form the phrasal verb are out, down, to, on, up, off, from, in, away and into. Based on the data we know that are phrasal verb in the novel and we know the different from phrasal verb and verb phrase in written form